Realization of the Ultrasonic Motor Speed Control System Based on H-Bridge - Tan Jiawan (Hindawi Limited, 2021)
In view of the requirement that the speed of rotor speed of ultrasonic motor can be stabilized quickly, combined with the mathematical model of two-phase traveling wave ultrasonic motor, we designed the rotor speed stability control strategy of the two-phase traveling wave ultrasonic motor based on voltage and current double feedback. We simulated, analyzed, and verified the designed strategy using Matlab/Simulink simulation tool. The rationality of the simulation results proves the correctness of the designed control strategy, which lays a theoretical foundation for the production design of two-phase traveling wave ultrasonic motor.